Monitoring Changes in the Tribological Behaviour of CrCN Thin Layers with Different CH4/N2 Gas Ratios at Room and Elevated Temperatures - Bakalova, Totka; Petkov, Nikolay; Bahchedzhiev, Hristo; Kejzlar, Pavel; Voleský, Lukáš (Manufacturing Technology Journal, 2018)
This research is engaged in monitoring changes in the tribological behaviour of CrCN thin films at room and elevated (300°C) temperatures. The monitored thin films are deposited by cathodic arc deposition of a pure Cr (99.99 %) cathode under an atmosphere of a mixture of CH4 and N2 gasses. Tribological measurements were performed at a load of 10N, a rotational speed of 60 rpm, and a counterpart of ceramic material (Al2O3). The article also describes the evaluation of wear on the studied thin films due to tribological measurement and temperature.
Keywords: Cathodic Arc Deposition; CrCN coatings; Surface Morphology; Tribology; Wear